1999
DOI: 10.1016/s0020-7292(99)00168-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Korean red ginseng on psychological functions in patients with severe climacteric syndromes

Abstract: Improvement of CMI and STAI scores in postmenopausal women suffering climacteric syndromes, particularly fatigue, insomnia and depression, by RG seemed to be brought about in part by effects of RG on stress-related hormones as shown by a decrease in C/D ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 14 publications
3
45
0
Order By: Relevance
“…Sparsely, ginseng has been reported to possess positive effects against herpes simplex type-II infections and diabetes mellitus, common cold symptom complex, ethanol-induced gastric lesion, and aspirin-induced gastric ulcers (131). Another study showed that ginseng helped postmenopausal women to alleviate climacteric syndromes, particularly fatigue, insomnia, and depression (132).…”
Section: Clinical Aspects Of Ginsengmentioning
confidence: 99%
“…Sparsely, ginseng has been reported to possess positive effects against herpes simplex type-II infections and diabetes mellitus, common cold symptom complex, ethanol-induced gastric lesion, and aspirin-induced gastric ulcers (131). Another study showed that ginseng helped postmenopausal women to alleviate climacteric syndromes, particularly fatigue, insomnia, and depression (132).…”
Section: Clinical Aspects Of Ginsengmentioning
confidence: 99%
“…4). Several models have been described that induce apoptosis using a number of different stimuli, such as, depriva-tion of growth factors (Wang et al, 2006), surface receptor-ligand binding (Tode et al, 1999), cytokines (Larrick and Wright, 1990), DNA damage (Kaufmann, 1989), and abortive cell cycle progression (Furukawa et al, 1996). The ability of a cell to undergo apoptosis in response to a death signal is related to its proliferative status, cell cycle position, and to the controlled expression of genes that affect the cell-death program.…”
Section: The Pkc Activator Tpa Prevented Cells From Costunolide-indmentioning
confidence: 99%
“…Thus, cell populations are controlled, autoreactive immune cells are eliminated, and virus-infected and neoplastic cells are killed by apoptosis (Jacobson et al, 1997). Furthermore, various exogenous and endogenous stimuli, such as, receptor-ligand interactions (Tode et al, 1999), radiation (Hendry et al, 1995), cytokine (Larrick and Wright, 1990), and anti-cancer drugs (Hickman, 1992) induce apoptosis, which characteristically results in chromatin condensation, the formation of apoptotic bodies, and DNA fragmentation. Furthermore, it has been shown that some cancer chemotherapeutics and chemopreventives exert their effects by triggering either apoptotic cell death or cell cycle transition, and thus, the induction of tumor cell apoptosis is used to predict tumor treatment response (Kim et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There is also very little data available on the efficacy and safety of many of these compounds, either used alone or in combination with other herbs. Table 2 [58][59][60][61][62][63][64][65][66][67][68][69] summarizes the available data on the clinical trials that have been conducted on these botanicals for menopausal women in specific. Trials conducted on non-menopausal populations are discussed in the text.…”
Section: Other Commonly Used Botanicalsmentioning
confidence: 99%
“…Both showed no estrogenic effects, no improvement in vasomotor symptoms, but improvement in somatic complaints (fatigue, insomnia, and depression) and a favorable effect on depression and well-being health subscales compared with placebo. [66,67] There is no consensus, but ginseng does not appear to have estrogenic activity by in vitro assay or in vivo biological assay although it is contraindicated in presence of breast cancer. [80] …”
Section: Ginseng (Panax Ginseng)mentioning
confidence: 99%